(3GdJPcQI GdfUjQjI (B_ (3aj Yde GdgjFIs - (3eMeO Hf eMeO Hf GdMSf, CHh LYaQ, fUjQ GdOjf GdWhSj , J (B672 (3g` s ((3eMeO MSjf GdbRhjfi GdehShi s)
(3ChdgG (B:s
(3GdMeO ddg eajV GdNjQ hedge GdUhGH fQjO Cf fhQO LedkG ef Yde GdgjFI JPcQI dHYV GdCMHGH adfhQO eG bUOfGg ai aUhd jTJed YdjgG CQHYI CHhGH s
(3BNQgG (B:s
(3hgh HYO GdKhGHJ ef eQcR GdCQV acGf NeSI hYTQjf Cda Cda hCQHY eFI , hGKfj YTQ Cda hKeGfi eFI hJSYI hJSYjf aQSNkG hdfNJe GdcJGH gGgfG MGeOjf ddg s
(3HgG fXGe GdJYbjHIs
(3HgG QShe gfOSjI HChdgG agQS ddaUhds
(3fSNI KGfjIs
(3JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGX hGdYHGQGJ s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
Keywords: (3Gdadcs